Effects of livestock grazing on nesting sage‐grouse in central Montana. Issue 7 (7th June 2018) - Smith, Joseph T.; Tack, Jason D.; Berkeley, Lorelle I.; Szczypinski, Mark; Naugle, David E.
ABSTRACT: Grazing by domestic livestock is ubiquitous in the sagebrush ( Artemisia spp.) biome of western North America. Widespread, long‐term population declines in greater sage‐grouse ( Centrocercus urophasianus ) have elicited concern about negative effects of livestock grazing on sage‐grouse populations. Hypothesized relationships, mostly untested, between livestock and sage‐grouse nesting ecology have played a prominent role in shaping public land livestock grazing policy and broader discussions about management of grazing in sagebrush ecosystems. We tested predictions arising from several commonly hypothesized mechanisms by which livestock may affect nesting habitat quality for sage‐grouse in a grazed landscape in central Montana, USA. We employed Bayesian variable selection methods to identify factors related to both nest site selection and nest success, focusing on indices of livestock use at local and pasture scales and including other factors known to influence nesting ecology such as anthropogenic features and weather. In spite of some evidence nest survival was positively associated with senesced vegetation height, evidence for effects of livestock presence and indices of local livestock use on nest site selection and survival was equivocal at best. In contrast, we found strong evidence that females selected nest sites based on relatively static features such as sagebrush cover and distance from gravel and paved roads, whereas nest failure was driven primarily by extended periods of heavy precipitation. Management of sage‐grouse nesting habitat in this region should focus on conserving areas of adequate shrub cover and preventing further fragmentation by roads. © 2018 The Wildlife Society. Abstract : We tested several hypotheses relating livestock grazing and herbaceous vegetation height and cover to sage‐grouse nest site selection and survival as part of a grazing experiment in central Montana, USA. Evidence for effects of grazing and herbaceous vegetation on nest site selection and survival was weak, whereas evidence for effects of shrub structure, roads, and weather was unequivocal.